Influence Of Chatgpt On Student Learning Behavior In Higher Education - Joshi, Kapil; Giri, Sanjana (Brixton Scholarly Review, 2026)
The rapid integration of artificial intelligence (AI) in the field of higher education has profoundly changed the learning process of students, especially with the implementation of generative AI tools like ChatGPT. However, little empirical evidence has been reported about the influence of AI tools on the learning behavior of students in developing countries like Nepal. The current study is aimed at exploring the influence of performance expectancy, effort expectancy, and social influence on the learning behavior of students with the help of the Unified Theory of Acceptance and Use of Technology (UTAUT) model. A quantitative research design was adopted, and the data were collected from 102 students of Nepal with the help of a structured questionnaire using a 5-point Likert scale. The results revealed that effort expectancy had a statistically significant positive impact on how students studied (β = 0.366, p 0.05). The results showed that this model could account for 64.1% of the significant variance in college students' learning behaviour (R² = 0.641). The results indicated that effort expectancy and social influence were generally more important to students in influencing their learning behavior compared with performance expectancy. This study has a number of crucial implications about how good AI tools can be successfully integrated into universities.